FloodSafeHome: evaluating financial benefits and savings of freeboard for improved decision-making in flood risk mitigation - Friedland, Carol J.; Lee, Yong-Cheol; Mostafiz, Rubayet Bin; Lee, Jiyoung; Mithila, Shifat P.; Rohli, Robert V.; Rahim, Md Adilur; Gnan, Ehab; Farris, Monica Teets (Frontiers in Communication, 2023)
Freeboard – elevation of a structure above the base flood elevation (BFE) – is a critical component in mitigating or avoiding flood losses. However, the unrevealed benefits and savings of freeboard installation have prevented communities from adopting this approach. To improve decision-making for residents, prospective residents, and other stakeholders in flood-vulnerable communities and enhance flood risk mitigation strategies, this study presents the methodology underlying a new webtool, FloodSafeHome, that estimates comprehensively the economic benefits and savings of freeboard installation for new construction of residential buildings. Specifically, the proposed evaluation framework has been designed to calculate monthly savings for individual buildings by assessing freeboard cost, insurance savings per year, and expected annual flood loss. This new evaluation method is built into a web-based, decision-making tool for use by the public and community leaders in three southeastern Louisiana parishes, to identify expected future benefits of building residences with freeboard and enhance their decision-making processes with interactive risk/benefit analysis features. For example, results indicate the levels of freeboard that optimize the cost-benefit ratio for flood-insured homes in the study area. This approach is expected to improve long-term flood resilience and provide cost-efficient flood mitigation strategies particularly in disaster vulnerable regions.